Stock markets and business cvycle comovement in Germany before World War I: Evidence from spectral analysis - Albrecht Ritschl; Martin Uebele (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper examines the comovement of the stock market and of real activity in Germany before World War I under the efficient market hypothesis. We employ multivariate spectral analysis to compare rivaling national product estimates to stock market behavior in the frequency domain. Close comovement of one series with the stock market enables us to decide between various rivaling business cycle chronologies. We find that business cycle dates obtained from deflated national product series are severely distorted by interference with the implicit price deflator. Among the nominal series, the income estimate of Hoffmann (1965) correlates best with the stock market, while the tax based estimate of Hoffmann and Müller (1959) is too smooth especially before 1890. We find impressive comovement between the stock market and nominal wages, a sub-series of Hoffmann's income estimate. We can show that a substantial part of this nominal wage series is driven by data on real investment activity. Our findings confirm the traditional business cycle chronology for Germany of Burns and Mitchell (1946) and Spiethoff (1955), and lead us to discard later, rivaling business cycle chronologies.
Keywords: E32; E44; N13; 330; Business Cycle Chronology; Imperial Germany; Spectral Analysis; Efficient Market Hypothesis; Konjunktur; Aktienmarkt; Einkommen; Lohn; Zeitreihenanalyse; Wirtschaftsgeschichte; Deutschland (bis 1945)